(untitled) - Meade, James W. (New York, 1989)
This book might be considered a farm management text for those in aquaculture. It is intended to provide an introduction to aquaculture principles and an introduction to management, including business and people management, microeconomics, and the concepts of efficiency and productivity.
Keywords: Nuôi trồng thủy sản,Aquaculture